The prevalence of panic disorder among English Class students at Medical Faculty, Universitas Udayana, Bali, Indonesia in 2018 - Thevarani Ramachandran; Ida Ayu Kusuma Wardani; Lely Setyawati (DiscoverSys Inc., 2019)
Background: Panic disorder is diagnosed in people who experience spontaneous, seemingly out-of-the-blue panic attacks and are very preoccupied with the fear of a recurring attack. Panic disorder usually begins in adulthood (after age 20) and can interfere a lot with daily life, causing people to miss work, go to many doctor visits, and avoid situations where they fear they might experience a panic attack. This study aims to determine the prevalence of panic disorder among English Class students at Medical Faculty, Universitas Udayana, Bali, Indonesia in 2018Methods: An observational cross-sectional study was conducted among 89 medical students from English Class at the Faculty of Medicine, Universitas Udayana in 2018 using total sampling techniques. A self-administered questionnaire was carried out to determine the prevalence of panic disorder by several valid and reliable questions. Data were analysed using SPSS version 20 for Windows and presented in frequency and percentage.Results: Â Most of the respondents were 20 years old (57.3%). There are only 12.0% of English class Semester 7 students are free from panic disorder, 51.0% suffers from mild panic disorder, and 37.0% suffers from moderate panic disorder. Around 64% of female respondents have panic disorder while 34% in male respondents. Female respondents are tended to get more panic attacks than male respondents in a ratio of 2:1.Conclusion: Female medical students tend to have a higher risk of panic disorder compared with males. The majority age of students suffering from panic attacks is from 20 to 23 years old.